THE EFFECT OF ANTI-TOBACCO POLICIES IN RUSSIA ON FILTERED CIGARETTES CONSUMPTION - Dyussembayeva, Gulnar (Nazarbayev University School of Sciences and Humanities, 2022)
In 2013, the anti-tobacco policy in the Russian Federation was changed substantially as a result of joining the WHO Framework Convention on Tobacco Control. This paper analyzes the effect of these anti-tobacco measures on cigarette consumption in the Russian Federation using the RLMS-HSE data. The results suggest that the average number of cigarettes, smoked daily by men, is estimated to decrease by approximately 1 cigarette as a result of the policy changes of 2013. However, the changes were less successful in decreasing the tobacco consumption of women
Keywords: Type of access: Open Access; anti-tobacco policy; cigarette consumption; Russian Federation